Evaluation of coincidence time resolution in a liquid xenon detector with silicon photomultipliers - N. Salor-Iguiñiz; J. M. Benlloch-Rodríguez; R. Esteve; V. Álvarez; F. Ballester; R. Gadea; J. Rodríguez; J. F. Toledo; R. Torres-Curado; V. Herrero; C. Romo-Luque; M. Querol; et al. (Physical Review Research)
This work explores the combination of liquid xenon as a scintillating medium and silicon photomultipliers as a readout in Positron Emission Tomography (PET) for enhanced Time-Of-Flight resolution. We present the results of our first prototype optimized to maximize light collection using high photodetection efficiency (PDE), VUV-sensitive sensors and to minimize time fluctuations. We report a coincidence time resolution of 281±2 ps FWHM, obtained using a ^{22}Na calibration source. This result is competitive with the current state-of-the-art PET scanners and represents a significant step forward in the development of liquid xenon as a viable alternative to conventional scintillators in PET technology.